THE IMPORTANCE OF FOREST REGENERATION IN PROTECTING ECONOMICALLY IMPORTANT TREE SPECIES - Gabriel Tonga, Noweg; Julia, Nelson (UNIMAS Publisher, 2023)
Bungo Range comprises of both primary forest in the upper highland and secondary forest in the lower part of the range. The primary forest has been gazetted as a national park on 26 February 2017, but there is very little information on the forest biodiversity on this range. The primary forest is divided into two types namely, kerangas forest (KF) and mixed dipterocarp forest (MDF). KF is also known as the tropical heath forest, which can be literally defined as the ‘land which cannot grow rice’ due to its highly acidic soil. The infertile soil has resulted in low yield of high-quality timber as compared to the MDF. The MDF, on the other hand, is mostly dominated by trees from the Dipterocarpaceae family. The Dipterocarpaceae trees yield high quality and expensive timber as compared to other timberproducing trees.